Feline cytauxzoonosis: reconsideration of pathophysiologic mechanisms - Kastl, Brandy C. (Kansas State University, 2022)
Feline cytauxzoonosis is a frequently fatal disease of domestic cats in the United States caused by the tick-transmitted protozoal hemoparasite Cytauxzoon felis. Feline cytauxzoonosis was first identified in southwestern Missouri in the early 1970’s and has since expanded into more northern regions of the United States. Clinical symptoms and death are largely attributed to C. felis schizogony within vascular-associated mononuclear cells. Yet, in-depth investigation of the pathophysiologic mechanisms of feline cytauxzoonosis have been hindered by ethical concerns with experimental infection and an inability to induce in vitro C. felis schizogony. Early reports attributed anemia with associated hyperbilirubinemia to extravascular hemolysis and death to vascular occlusion by C. felis schizont-laden macrophages, ischemic injury, and disseminated intravascular coagulation. Furthermore, some publications suggest a link between infecting C. felis strain with patient morbidity and mortality. Recently, immunohistochemical and serologic evaluation of localized and systemic pro-inflammatory cytokine responses in acute feline cytauxzoonosis prompted nuanced reconsideration of pathophysiologic mechanisms for illness and death in affected cats. Here, serum biochemical abnormalities were utilized as a method of assessing pathophysiologic mechanisms in acute feline cytauxzoonosis. In addition, several projects aimed at understanding the pathophysiologic mechanisms of disease in feline cytauxzoonosis are proposed. Assessment of hematologic and serum biochemical abnormalities is routinely employed in veterinary medicine. Alterations in concentrations of individual analytes and patterns involving several analytes provide clinicians guidance on underlying pathophysiologic mechanisms. Thorough descriptions and assessments of serum biochemical abnormalities in domestic cats infected with C. felis are lacking, or sometimes contradictory, in published literature. Here, serum biochemical abnormalities were retrospectively assessed in 28 naturally infected domestic cats to determine common abnormalities and patterns of acute feline cytauxzoonosis. Results were then compared to those of two feline disorders which may have similar clinical presentations in domestic cats, hepatic lipidosis and cholangiohepatitis. Acute feline cytauxzoonosis was characterized by nonregenerative anemia (20/28, 71.4%), leukopenia (23/28, 82%), thrombocytopenia (23/23, 100%), hyperbilirubinemia (27/28, 96.6%), hypoalbuminemia (26/28, 93%), reduced (18/28, 64%) or low normal (10/28, 36%) serum ALP activity, and hyponatremia (23/28, 82%). No correlation between severity of anemia and magnitude of hyperbilirubinemia in feline cytauxzoonosis patients was identified. Feline cytauxzoonosis was associated with statistically significant (p<0.05) decreases in hemoglobin, total leukocyte, and platelet concentrations when compared to hepatic lipidosis and cholangiohepatitis patients. Reduced ALP activity was unique to cats with feline cytauxzoonosis and the decreased serum ALP activity was significantly lower (p<0.05) than in hepatic lipidosis and cholangiohepatitis. Furthermore, feline cytauxzoonosis patients had higher total bilirubin concentrations (p<0.05) than those with hepatic lipidosis and cholangiohepatitis. The overall pattern of hematologic and serum biochemical profile changes in cats with feline cytauxzoonosis is similar to those reported in feline bacterial sepsis, including nonregenerative anemia, hyperbilirubinemia, and reduced serum ALP activity. As feline cytauxzoonosis is simply a form or protozoal sepsis with similar pro-inflammatory cytokine responses as those reported in feline bacterial sepsis, these similarities are not unexpected. However, the decoupling of the degree of anemia and magnitude of hyperbilirubinemia in feline cytauxzoonosis patients suggests that extravascular hemolysis, while present, is not likely the only pathophysiologic mechanism for development of hyperbilirubinemia in septic cats. Reduced hepatocellular bile excretion mediated by pro-inflammatory cytokines, a process known as functional or inflammation-induced cholestasis, may be occurring in septic cats. Previous publications have excluded functional cholestasis as a possibility due to the absence of increased serum ALP activity in cats, as observed in humans and dogs. Furthermore, reduced serum ALP activity is often ignored in serum biochemical profile panels as “clinically insignificant”. Yet, the repeatability of this abnormality in both bacterial and protozoal sepsis warrants reconsideration of the diagnostic utility of low serum ALP activity and the expectation that cats should have increased serum ALP activity with functional cholestasis. Future research stemming from questions regarding the pathophysiologic mechanisms of feline cytauxzoonosis based on serum biochemical abnormalities are proposed. The first proposal is an investigation into histologic and immunohistochemical evidence of functional cholestasis in formalin-fixed, paraffin-embedded liver sections of cats afflicted with feline cytauxzoonosis. This proposal will use immunohistochemical labeling for the pro-inflammatory cytokines, IL-6, TNF-α, and IL-1β, known to induce functional cholestasis in cats as well as the two transport proteins these cytokines down-regulate, multidrug resistant protein 2 (MRP2) and bile salt export pump (BSEP). The second proposed project will look at the hematologic and serum biochemical profiles of a larger cohort of feline patients with bacterial, protozoal, fungal, and viral sepsis and non-infectious systemic inflammatory response syndrome to determine if there are similar serum biochemical patterns between all causes of systemic inflammation in feline patients. Finally, evaluation of the association between C. felis strain and clinical outcomes is proposed comparing C. felis strains identified in formalin-fixed tissues of deceased domestic cats to those of a large population of recently identified C. felis carriers in Kansas.
Keywords: Cytauxzoonosis; Cytauxzoon felis; Serum biochemistry; Functional cholestasis; Pathophysiology; Alkaline phosphatase